Translation Techniques in Environmentally Oriented Short Story Hinoki to Hinageshi (Pohon Hinoki dan Bunga Hinageshi) by Miyazawa Kenji into Indonesian - Kusmiati Dewi (EDP Sciences, 2021)
This study analyzed the translation techniques of Miyazawa Kenji's Hinoki to Hinageshi, which were translated to Indonesian as “Pohon Hinoki dan Bunga Hinageshi” by the UNPAD Press translation team. This short story tells about the life of a Hinoki tree with Hinageshi flowers that want to become a star, until one day a demon incarnates who wants to take advantage of Hinageshi flowers. In this short story, there are words that have a direct equivalent in Indonesian and those that do not have a direct word equivalent, so the aim of this study is to find the translation techniques used when translating this short story. The theory used is the theory of translation techniques by Hoed (2006), and data were collected using the literature review method. The collected data were analyzed with a distributional method. There are 7 types of translation techniques used by the translator: 1) Transposition, 2) Modulation, in the form of shifted meaning and a shift in the scope of meaning, 3) Descriptive Translation, 4) Contextual Conditioning, 5) Official/Standard Translation, and 6) Cultural Equivalent.